Pentraxins and IgA share a binding hot‐spot on FcαRI. (28th January 2014) - Lu, Jinghua; Marjon, Kristopher D.; Mold, Carolyn; Marnell, Lorraine; Du Clos, Terry W.; Sun, Peter
Abstract The pentraxins, C‐reactive protein (CRP), and serum amyloid P component (SAP) have previously been shown to function as innate opsonins through interactions with Fcγ receptors. The molecular details of these interactions were elucidated by the crystal structure of SAP in complex with FcγRIIA. More recently, pentraxins were shown to bind and activate FcαRI (CD89), the receptor for IgA. Here, we used mutations of the receptor based on a docking model to further examine pentraxin recognition by FcαRI. The solution binding of pentraxins to six FcαRI alanine cluster mutants revealed that mutations Y35A and R82A, on the C‐and F‐strands of the D1 domain, respectively, markedly reduced receptor binding to CRP and SAP. These residues are in the IgA‐binding site of the receptor, and thus, significantly affected receptor binding to IgA. The shared pentraxin and IgA‐binding site on FcαRI is further supported by the results of a solution binding competition assay. In addition to the IgA‐binding site, pentraxins appear to interact with a broader region of the receptor as the mutation in the C′‐strand (R48A/E49A) enhanced pentraxin binding. Unlike Fcγ receptors, the H129A/I130A and R178A mutations on the BC‐ and FG‐loops of D2 domain, respectively, had little effect on FcαRI binding to the pentraxins. In conclusion, our data suggest that the pentraxins recognize a similar site on FcαRI as IgA.